The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1210/endo-114-5-1657
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Ability of Old Male Rats to Secrete Luteinizing Hormone (LH) Is Not due to Alterations in Pituitary LH-Releasing Hormone Receptors*

Abstract: The present study was undertaken to determine if the diminished release of LH in male rats with age in response to castration or LHRH injection is due to alternations in the number or affinity of LHRH receptors in the pituitary. Young (3-4 months old) and old (18-20 months) male Sprague-Dawley rats were killed 0, 2, 4, and 8 days after castration. Serum was collected for determination of LH concentrations, and anterior pituitaries were removed for analysis of LHRH receptors. The numbers and affinity constants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Previous studies have found that LH levels increase after gonadectomy and the increase is greater in young than in old males. Moreover, LH is suppressed by T treatment in both young and old males, but old males are more sensitive to low doses of T than young males (Karpas, Bremner, Clifton, Steiner, & Dorsa, 1983; Pirke, Geiss, & Sintermann, 1978; Sartin & Lamperti, 1984; Shaar, Euker, Riegle, & Meites, 1975; Sonntag, Forman, Fiori, Hylka, & Meites, 1984). Although the mean levels of LH were higher in the young GX males than in the old GX males, in this study this difference did not achieve significance.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have found that LH levels increase after gonadectomy and the increase is greater in young than in old males. Moreover, LH is suppressed by T treatment in both young and old males, but old males are more sensitive to low doses of T than young males (Karpas, Bremner, Clifton, Steiner, & Dorsa, 1983; Pirke, Geiss, & Sintermann, 1978; Sartin & Lamperti, 1984; Shaar, Euker, Riegle, & Meites, 1975; Sonntag, Forman, Fiori, Hylka, & Meites, 1984). Although the mean levels of LH were higher in the young GX males than in the old GX males, in this study this difference did not achieve significance.…”
Section: Discussionmentioning
confidence: 94%
“…As matured rats are reported to be stable at the level of estrogen in an ovariectomized animal model [16, 17], relatively young rats (10-week old, approximately 230 g) in the growth stage were used in this study to examine the SMF effects on the concentration change of estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…At the pituitary level, the impaired gonadotrophin response to LHRH observed in old rats [7] is not associ ated with changes in the number of LHRH receptors [44], but no data are presently available pertaining to LHRH accumulation and processing in the adenohypo physis of old rats. Moreover, variant forms of gonadotro phins have been detected in the pituitary gland of old rats, suggestive of changes with age in the biological activity of the hormones [45],…”
Section: Aging and Reproductive Functionmentioning
confidence: 98%